Multiplex Real-Time PCR Assay Targeting Eight Parasites Customized to the Korean Population: Potential Use for Detection in Diarrheal Stool Samples from Gastroenteritis Patients. - Eun Jeong Won; Soo Hyun Kim; Seung Jung Kee; Jong Hee Shin; Soon Pal Suh; Jong Yil Chai; Dong Wook Ryang; Myung Geun Shin (PLoS ONE, 2016)
Intestinal parasitic diseases occur worldwide and can cause diarrhea or gastroenteritis; however, their diagnosis is quite difficult, especially in low-endemism countries. We developed a multiplex real-time PCR assay for detection of eight intestinal parasites and prospectively evaluated it for patients with gastroenteritis. The assay targeted Cryptosporidium parvum, Giardia lamblia, Entamoeba histolytica, Blastocystis hominis, Dientamoeba fragilis, Clonorchis sinensis, Metagonimus yokogawai, and Gymnophalloides seoi. Performance characteristics were evaluated based on recovery after DNA extraction, analytical sensitivity, specificity, reproducibility, cross-reactivity, and interference characteristics. Clinical performance was validated against microscopy on 123 diarrheal samples. The assay demonstrated strong correlations between DNA concentrations and Ct values (R2, 0.9924-0.9998), and had a high PCR efficiency (83.3%-109.5%). Polymerase chain reactions detected as few as 10-30 copies of genomic DNA, and coefficient of variance was 0-7%. There was no cross-reactivity to the other 54 microorganisms tested. Interference occurred only in presence of high concentrations of erythrocytes or leukocytes. This assay had a higher correct identification rate (100.0% vs. 90.2%) and lower incorrect ID rate (0.0% vs. 9.8%) when compared to microscopy. Overall, this assay showed a higher sensitivity (100.0%; 95% confidence interval [CI] of 80.5-100.0) than microscopy (29.4%; 95% CI 10.31-55.96), and the specificity levels were comparable for both methods (100.0%; 95% CI 96.58-100.0). This newly developed multiplex real-time PCR assay offers a potential use for detecting intestinal parasitic pathogens customized to the Korean population.